Colombian Anthology for Flute and Piano: Danza, Intermezzo, Pasillo and Bambuco - Castro-Turriago, Jesús Augusto; Cáceres Rueda, Sandra Bibiana; Lizcano Caro, José A. (2025)
This book presents a comprehensive music research project led by the author in collaboration with the Music, Education, Culture, and Society Research Team of Pamplona University, as well as the Linguartic and Servipúblico Research Teams of the District University Francisco José de Caldas. The study seeks into the traditional Andean Colombian musical styles of danza, intermezzo, pasillo, and bambuco, examining their distinctive musical and aesthetic characteristics through an indepth analysis of selected works by prominent 20th-century and modern Colombian composers from the Andean region.These composers include Luis Antonio Calvo, Sebastián Solari, Luis Uribe Bueno, Jaime Romero, Luis Carlos Saboya, León Cardona, José Revelo Burbano, and Gentil Montaña, each contributing significantly to the development of Colombian music. The analyzed repertoire includes Adiós a Bogotá (danza), Intermezzo No. 1 (intermezzo), pasillos such as Río Cali, El cucarrón, Bandolita, La fantasía del escribano, and ¡Despasillo por favor!, along with bambucos such as Bambuquísimo, Fantasía en 6/8, and El tolimense. Beyond exploring the music, the book offers biographies of these composers, and contributions to Colombia’s cultural heritage. To further support performers and researchers, the book provides sheet music for flute and piano, featuring arrangements by Jesús Castro. This combination of historical context, musical analysis, and practical resources makes the book a valuable contribution to the understanding and appreciation of Andean Colombian music and its rich traditions.
Keywords: Music; Music Performance; Colombian Music; Flute and Piano performance; Colombian Composers; Danza; Intermezzo; Pasillo; Bambuco